THE EFFECT OF SUSTAINABILITY ACCOUNTING ON FINANCIAL PERFORMANCE WITH TRANSPARENCY AS A MODERATOR - Charly Manurung; Endang Ruhiyat; Suripto (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study was conducted to see the influence of sustainable accounting on the financial performance of companies with transparency as a moderator in financial sector companies listed on the Indonesia Stock Exchange from 2020 – 2022. This study uses secondary data with a sample of 129 companies selected by the purposive sampling selection method. The analysis used in this study is a panel data regression test using the EViews 12 program. The results of this study show that sustainable accounting has an effect on the company's financial performance as measured by ROE (Return On Equity) but does not affect ROA (Return On Assets) and ROI (Return On Investment) and transparency moderates the relationship between sustainability accounting and ROE and ROI but transparency does not moderate the relationship between sustainability accounting and ROA.